Navigating Recognition: The Symbolic Struggles in the Biographies of Young Polish Internet Content Creators - Łuczaj, Kamil (Qualitative Sociology Review, 2025)
This paper aims to examine the symbolic struggles embedded in the biographies of internet content creators. Pursuing a relatively new profession that lacks symbolic legitimization necessitates both explanatory and emotional labor to justify a “biographical action scheme” that does not align with existing “institutionalized schedules for organizing biographies,” in Fritz Schütze’s sense. Drawing on interviews with young Polish internet content creators, I analyze these struggles through the lens of Axel Honneth’s concept of the “struggle for recognition” and Michèle Lamont’s notion of “symbolic boundaries.”The empirical analysis suggests that the initial struggle involves proving their worth to close family and friends, who may question the legitimacy of being an influencer compared to a stable 9-to-5 job. This tension is particularly pronounced in intergenerational relationships, such as between children and their parents. The second struggle occurs between content creators and their audiences. Here, the challenge is defending oneself against justified or unjustified accusations and hate speech. The third struggle is inherent to those operating at the intersection of various social fields. For these influencers, who build their content on popular science, the lack of recognition or hostility from the academic community is another serious biographical problem.The necessity to engage in constant power struggles, which demand considerable skill, challenges the widespread perception of internet influencing as a “childish” profession—one that offers an enjoyable job paired with undeservedly high earnings.